Tafsir Ijmali as an Initial Method in Interpreting the Al-Qur'an - Fuad Salim; Thariq Ibrahim; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2026)
The interpretation of the Qur'an has started since the time of the Prophet Muhammad SAW and continues to this day. Every interpretation product produced from the time of the Prophet SAW to the present day must have different approaches and conclusions. This is due to the fact that the need for interpretation at any time is always changing. This article aims to reveal the historical aspects of the emergence, basis, urgrnsi, steps and characteristics of the ijmali interpretation method. This research is a library research using qualitative method. The results of this study indicate that the ijmali interpretation method is one of the approaches in the interpretation of the Qur'an that developed since the early period of Islam, along with the needs of the people to understand the messages of the Qur'an simply and thoroughly. Historically, this method was used by the companions and previous scholars in explaining the meaning of the verses of the Qur'an without going into too much detail word by word, making it easier to be accepted by the laity. The importance of this method lies in its ability to convey the Qur'anic message in a concise yet thorough manner, making it an effective means of building a basic understanding of the Qur'an for readers from various backgrounds. Conveying the global meaning of the verse, maintaining the continuity of the narrative without focusing on in-depth linguistic analysis or grammatical aspects, is the hallmark of the ijmali method. As such, it is well suited for conveying the core teachings of Islam and the moral message of the Qur'an, especially in the context of education and dissemination of Islamic teachings to the wider community.